A metering network for a smart prepaid scheme under an electrical utility organization - Saiara, Syeda Afra (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.